2019
DOI: 10.1002/mus.26722
|View full text |Cite
|
Sign up to set email alerts
|

Multiphasic presentation of neuralgic amyotrophy associated with hepatitis E virus infection

Abstract: Background: The aim of this study was to further characterize the clinical phenotype of hepatitis E virus (HEV)-associated neuralgic amyotrophy (NA).Methods: Three patients with HEV-associated NA underwent clinical, electrodiagnostic, and ultrasound assessment.Results: In all patients, symptoms developed in several phases within a time span of 4-6 weeks, with three or more nerves involved. Symptoms were bilateral in two. In two patients, nerves of the trunk and the lower limb were affected as well. In one pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…HEV is commonly found in pork-derived food products, which suggests a potential role for increased vigilance from the authorities. It causes an extensive phenotype that may present with multiphasic symptoms [44 ▪▪ ]. As HEV rarely causes hepatitis and no difference in outcome was found in HEV- positive NA patients that did or did not receieve ribavirine, no specific antiviral treatment seems needed in this group [18].…”
Section: Pathophysiology and Immunological Triggersmentioning
confidence: 93%
“…HEV is commonly found in pork-derived food products, which suggests a potential role for increased vigilance from the authorities. It causes an extensive phenotype that may present with multiphasic symptoms [44 ▪▪ ]. As HEV rarely causes hepatitis and no difference in outcome was found in HEV- positive NA patients that did or did not receieve ribavirine, no specific antiviral treatment seems needed in this group [18].…”
Section: Pathophysiology and Immunological Triggersmentioning
confidence: 93%
“…8,[24][25][26] In addition, reports regarding hepatitis E virus leading to brachial plexus neuritis have increased significantly. 27,28 In the recommendations for early treatment, no researcher has directly recommended antiviral treatment unless there is a clear evidence of viral infection. Neurophysiologists have reported that herpes zoster virus can cause typical brachial plexus neuritis.…”
Section: Discussionmentioning
confidence: 99%
“…Особенностью представленного наблюдения является двустороннее поражение плечевого сплетения, тогда как в подавляющем большинстве случаев НА страдает одна сторона плечевого пояса [3,4]. Кроме того, при билатеральном поражении болевой синдром возникает одновременно с обеих сторон [3], тогда как у нашего больного боль в другом плече появилась с интервалом в сутки.…”
Section: Discussionunclassified
“…Кроме того, при билатеральном поражении болевой синдром возникает одновременно с обеих сторон [3], тогда как у нашего больного боль в другом плече появилась с интервалом в сутки. Двустороннее поражение плечевого сплетения при НА требует исключения таких состояний, как гепатит Е, ВИЧ-инфекция, Лайм-боррелиоз [4][5][6]. Однако развитие НА у пациента в зимний период позволило не проводить обследование крови и ликвора на наличие антител к боррелиям, с учетом того, что последнее размножение иксодовых клещей наблюдается в конце августа -начале сентября, когда возможно получить укус клеща, и 2-я фаза Лайм-боррелиоза (т.е.…”
Section: Discussionunclassified